2014
DOI: 10.1186/1471-2334-14-507
|View full text |Cite
|
Sign up to set email alerts
|

“Fighting an uphill battle”: experience with the HCV triple therapy: a qualitative thematic analysis

Abstract: BackgroundHepatitis C virus (HCV) infections are a severe burden on public health worldwide, causing mortality rates triple that of the general population. Since 2011, for both therapy-naive and therapy-experienced genotype 1 patients, the first generation of direct acting antivirals (DAAs), i.e., the protease-inhibitors (PI) telaprevir and boceprevir have been added to existing dual therapies. The therapeutic effect of the resulting triple therapy is striking; however, treatment regimens are complex and commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…All ten studies were conducted in high-income, Western countries. One study examined adherence to interferon only, [ 27 ] eight studies examined interferon and ribavirin regimens [ 10 , 12 , 28 33 ] and one study examined DAA triple therapy adherence [ 34 ]. A description of these studies can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All ten studies were conducted in high-income, Western countries. One study examined adherence to interferon only, [ 27 ] eight studies examined interferon and ribavirin regimens [ 10 , 12 , 28 33 ] and one study examined DAA triple therapy adherence [ 34 ]. A description of these studies can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A description of these studies can be found in Table 2 . These studies represent data from 525 participants and were conducted through in-depth interviews, [ 10 , 12 , 27 30 , 32 34 ] focus groups, [ 12 , 30 , 32 ] and personal narratives [ 31 ]. The number of participants in each study ranged from 2 to 164.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations